Cortisol sanguíneo e qualidade de carcaças de frangos abatidos pelo método halal ou com insensibilização por eletronarcose - Mendes, Paulo Vinícius da Costa [UNESP] (2015)
Brazil is the largest exporter and third largest producer of broiler chickens, prominent position due to the meet the demands of consumers markets with incisive requirements, with investments in environmental sustainability and animal welfare. The countries of Islam have considerable importance for Brazilian exports. This study aimed to assess blood cortisol and chicken carcass quality slaughtered by the Halal method - own service this market without stunning, as required by Islam and compare them to numb by electro, according to humanitarian normal slaughter. Serum levels of blood cortisol using a commercial kit was performed in chickens slaughtered in fridge with SIF in the southwest region of the state of Goiás, to assess the immediate stress, ie at the time of slaughter, and the experimental design was completely randomized. Also evaluated the quality of animal housing slaughtered by both methods, trying to identify skin changes, attachments, muscles, bones and joints that show non-compliance with the animal welfare standards, depreciating therefore the carcass quality. It was found that there was a statistical difference between the different methods of slaughter, presenting a lower stress level of the animals, the method Halal and higher quality castings with the use of prior stunning for electro, followed by automatic sangria. We conclude that the animal welfare point of view, both slaughter methods still offer challenges to be understood and overcome. The traditional method of killing seems to take better account of animal welfare provisions due to the use of stunning animals, although a number of tecnopatias can depreciate the quality of carcasses.